An assessment of Canadian systems for triaging referred out genetic testing. (26th July 2014) - Christian, S.; Blumenschein, P.; Lilley, M.
<x xml:space="preserve">Abstract</x> The field of genetics is evolving rapidly, significantly expanding the number of clinically useful genetic tests. The cost of genetic testing has created an increasing burden on public health care budgets. In Canada, funding bodies have responded by developing independent systems. Key individuals in each province and territory participated in a semi‐structured interview regarding the process in their jurisdiction to approve funding for referred out genetic testing and their decision‐making criteria. Two themes were identified: the importance of clinical utility in decision‐making and the utilization of genetic specialists as gate keepers. Allocation of a specific budget appears to be associated with some fiscal responsibility. Collaboration between provincial and territorial bodies may lead to a more unified approach across Canada.